An Estimate of Resource Expenditures on Transfer Activity in the United States - Laband, D. N.; Sophocleus, J. P. (Quarterly Journal of Economics, 1992)
This paper details resource expenditures on nonexchange, noncharity transfer activity in the United States in 1985. Expenditures designed to facilitate and inhibit nonexchange transfers, executed privately or through the state, are reported. The numbers indicate that individuals plausibly invested nearly a trillion dollars in transfer activity that year. Nominal GNP in 1985 was just over $4 trillion, which includes numerous transfer-related resource investments that arguably should be subtracted out. Transfer activity thus apparently constitutes a much larger fraction of all economic activity conducted in the United States than previously recognized.